Learning design in diverse institutional and cultural contexts: suggestions from a participatory workshop with higher education professionals in Africa. (2nd September 2018) - Mittelmeier, Jenna; Long, Dianne; Cin, Firdevs Melis; Reedy, Katharine; Gunter, Ashley; Raghuram, Parvati; Rienties, Bart
ABSTRACT: Learning design approaches, such as those adopted by the Open University, provide a set of tools and resources for purposefully-designing modules with a focus on student experiences. However, many of the current learning design strategies have been situated within specific institutions in Europe and North America. This means that there are several issues worth considering around if and how established learning design approaches make sense in diverse institutional and cultural contexts. To critically assess the relevance and appropriateness of learning design strategies in new contexts, this article describes an in-depth participatory workshop with 34 education professionals from five African countries. Altogether, 10 suggestions for learning design practices were derived from the consensus of workshop participants, which provide a foundation for the development of learning design practices moving forward.